2011
DOI: 10.2174/1874829501104010040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Pollution Levels in the Nyabugogo Catchment, Rwanda

Abstract: This study aims to develop a comprehensive system of pollution monitoring and control in the Nyabugogo catchment of Rwanda, which also includes the capital city, Kigali, through locating and highlighting pollution and its sources. Pollution hotspots were identified, covering areas of both anthropogenic and natural pollution. The study focused on water quality assessment especially the identification of the critical points of pollution , pH, and Turbidity. The samples were collected, preserved and analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 7 publications
10
34
3
Order By: Relevance
“…It is later fed by other rivers from the urbanized parts of Kigali such as Rwanzekuma, Ruganwa, Mpazi and Yanze. Floriculture, sugar processing at Kabuye works sugar industry, sugar cane plantations, agrarian and mining activities along this river are the major sources of anthropogenic pollution [8].…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…It is later fed by other rivers from the urbanized parts of Kigali such as Rwanzekuma, Ruganwa, Mpazi and Yanze. Floriculture, sugar processing at Kabuye works sugar industry, sugar cane plantations, agrarian and mining activities along this river are the major sources of anthropogenic pollution [8].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The pH values recorded in this study agreed well with those recorded by previous reports. Nhapi et al [8] reported a pH of 7.24 ± 0.18 at Rwesero, the first point after Nyabugogo river flows out of Lake Muhazi. Further, a more or less constant pH in Nyabugogo swamp was reported [11] and the author implicated this to be the effect of high pH of water in Rwanzekuma and Ruganwa rivers which receive alkaline reagents from Usine Textile Du Rwanda (UTEXRWA) textile industry and other factories in Kigali city.…”
Section: Physicochemical Profile Of Water From Nyabarongo and Nyabugomentioning
confidence: 99%
See 2 more Smart Citations
“…This however, affects the municipal wastes management due to informal settlements, expansion of the city and industrialization whose final results is water quality degradation and pollution as well (Mohammed et al, 2017;Uwimbabazi, Lawrence, 2011). Despite the present Governmental initiative (which is not yet fully completed) of re-allocating industries from or near watersheds to appropriate and well equipped location (Rwanda Special Economic Zone), their former location led to immense wetland and biodiversity degradation (Etale, Drake, 2013;Nhapi et al, 2011). In addition, the report of the Kigali City Conceptual Master Plan (Kigali…, 2007) indicates that the city will keep expanding in size and its inhabitants will almost triple in the next 25 years.…”
Section: Urbanization and Industrializationmentioning
confidence: 99%